Students’ Perceptions About What Aspects Can Make Them Like to Learn The Science - Sitti Jauhar; Muliadi Muliadi; Adnan K.; Sudarto Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This research was a survey method that aimed to find out the students’ perception about the aspects that can make them happy to learn the Science. Amount of the samples: 74 people . The data was collected by using questionnaire and interview technique and processed using descriptive statistics. Result: There are seven aspects that can make the students happy in learning the Science: awareness of the need to learn the science, the science contents are about our selves, the way of the teacher/lecturer in teaching the science is fun, Science makes us understand abut the nature, Science makes us getting know the animals and the plants better and better, Science material is exact, and the exictence of the encouragement or parental attention. Conclusion: Abaout the students, there are seven aspects that can make them happy in learning the Science.